2003
DOI: 10.1074/jbc.m208098200
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Binding Mode of a Ribosome Recycling Factor (RRF) from Mesophilic Bacterium

Abstract: X-ray and NMR analyses on ribosome recycling factors (RRFs) from thermophilic bacteria showed that they display a tRNA-like L-shaped conformation consisting of two domains. Since then, it has been accepted that domain I, consisting of a three-helix bundle, corresponds to the anticodon arm of tRNA and domain II and a ␤/␣/␤ sandwich structure, corresponds to the acceptor arm. In this study, we obtained a RRF from a mesophilic bacterium, Vibrio parahaemolyticus, by gene cloning and carried out an x-ray analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 41 publications
7
50
0
Order By: Relevance
“…The L-shape of the RRF density in the cryo-EM map ( Fig. 1) is consistent with crystal (9,11,13) and solution (12) structures of RRF from various species. Independent docking of all these atomic structures into the EM density shows that the density is best explained by the crystallographic structure of the Thermotoga maritima RRF (Fig.…”
Section: Comparison Of Atomic Structures Of Rrf With Corresponding Crsupporting
confidence: 59%
See 1 more Smart Citation
“…The L-shape of the RRF density in the cryo-EM map ( Fig. 1) is consistent with crystal (9,11,13) and solution (12) structures of RRF from various species. Independent docking of all these atomic structures into the EM density shows that the density is best explained by the crystallographic structure of the Thermotoga maritima RRF (Fig.…”
Section: Comparison Of Atomic Structures Of Rrf With Corresponding Crsupporting
confidence: 59%
“…Atomic structures of RRF determined from five different species, including Escherichia coli, show that it is comprised of two structural domains: domain I, consisting of three long ␣-helix bundles, and the smaller domain II, which is an ␣͞␤ motif (9)(10)(11)(12)(13). Different orientations of domain II in these structures have been attributed to interdomain flexibility, which is thought to be necessary for RRF to function on the ribosome (12).…”
mentioning
confidence: 99%
“…Crystal and solution structures of RRF from several different organisms show that it is composed of two domains that adopt an "L" configuration [13][14][15][16][17][18][19] . Domain I of RRF is composed of a three-helix bundle ( Figure 2) that interacts with the large subunit of the ribosome 20-22 .…”
Section: Introductionmentioning
confidence: 99%
“…The three ␣-helices are arranged with a very rare right-handed twist. We found that, by using the DALI server (19,20), this helical arrangement has only been seen before for domain I of the ribosome recycling factor from different prokaryotic organisms (21)(22)(23)(24)(25).…”
Section: Conformational Heterogeneity Of Ahsp-thementioning
confidence: 98%